Enhancing market efficiency for chili farmers through digital auction platforms: A case study of semar-dica apps - Hasan, Nugroho; Eksa Rusdiyana; Anwar, Syaiful (Journal of Sustainability, Society, and Eco-Welfare, 2025)
Background: The red chili supply chain in the coastal sandy areas of Kulon Progo, Yogyakarta, faces chronic inefficiencies, including volatile prices, lengthy distribution channels, and farmers’ dependency on intermediaries. Although traditional auction markets offer more transparent price formation, delayed payments often push farmers back into unfavorable marketing practices. The advancement of digital technology provides new opportunities to enhance market efficiency and empower smallholder farmers. This study aims to analyze the implementation of the Semar-Dica Apps, an Android-based digital auction platform, to design an effective digital marketing system and evaluate its potential to improve market efficiency and farmers’ income . Methods: A qualitative descriptive approach was employed, supported by participatory action research (PAR) in several chili-producing villages of Panjatan Sub-district, Kulon Progo. Data were collected through field observations, in-depth interviews with key stakeholders, and analysis of relevant secondary data. The analysis involved thematic coding, comparison between conventional and digital auction mechanisms, SMART feasibility assessment, and stakeholder mapping using the Triple Helix model. Findings: The Semar-Dica platform demonstrates potential in shortening supply chains, increasing price transparency, and accelerating payment processes. However, challenges remain, including limited digital literacy, operational costs, and competition with local traders. To overcome these barriers, farmer training, video-based guidance, and inclusive stakeholder engagement are necessary. Collaboration with local collectors is also suggested to support smoother adoption. Conclusion: The Semar-Dica Apps offer a promising solution for enhancing market efficiency and improving income security for chili farmers. Its success, however, relies on strategic implementation and support from all stakeholders. Novelty/Originalty of this article: This study contributes to the discourse on agricultural digitalization by identifying context-specific barriers to adoption and offering targeted, inclusive strategies to facilitate the transition of smallholder farmers to digital marketing platforms